Social encouragement can influence manual preference in 6 month-old-infants - Morange-Majoux, Françoise; Devouche, Emmanuel (Frontiers in Psychology, 2014)
The purpose of this study was to investigate the influence of social encouragement on manual motricity, in particular on manual preference. Thirty-six infants were observed at 5.5 months. In a first step, their spontaneous manual preference was recorded with an object placed on the midline position; then, the second step consisted in leading infants to use their non-preferred hand by putting the object near that hand and congratulating them. The third step was similar to the first one (object placed on the midline position) except that the infant continued to be congratulated when (s)he used the non-preferred hand for reaching the object. Results showed that half of the infants exhibited a spontaneous manual preference. A majority of these infants could use their non-preferred hand if they were verbally encouraged. Moreover, spontaneously left-handed infants modified their hand-use more easily than right-handed infants. Although our findings only show a momentary influence of the social context in a short term, results are discussed in a more socio-cognitive perspective, where social encouragements can model manual preference, in particular its strength and its stability.